Recent claims of China's economic exceptionalism: Reflections inspired by WTO accession - Wing Thye Woo (University of California, Department of Economics, 2001)
The desirability of WTO membership for China depends on whether its economic successes have been the result of its discovery of new institutional forms (e.g. dual track pricing, SOE contracts, and fiscal contracts) that are optimal for China''s particular economic circumstances, or have been the result of the convergence of its economic institutions to those of a typical advanced member of WTO. If the experimentalist interpretation of China''s phenomenal growth is correct, then WTO membership is a negative development because it could be a straitjacket for WTO-enforced institutional harmonisation that would constrain China''s scope for experimentation. But if the experimentalist interpretation is wrong, then WTO membership is a positive development that will lock China on to the path of deepening economic reform. We assess several recent claims of China''s economic exceptionalism, and conclude that they neglected the considerable costs associated with the use of these innovative mechanisms (which have led to the repeal of every one of these optimal mechanisms) and that these mechanisms were unlikely to have produced positive results in the transition economies in Europe. Because a major reason for the failure of Gorbachev''s reforms was opposition from the entrenched interests within the ruling structure, China''s forthcoming WTO accession could be seen as an attempt by reformers to lock economic policies on to a market-oriented course that is costly to reverse.
Keywords: H30; O11; O40; O53; P20; P22; P26; P31; P52; 330; Economics of Transition; WTO; Economic Reform in China; Dual Track Pricing; State Enterprise Reform; Privatization; Fiscal System; Convergence School; Experimentalist School; Internationale Wirtschaftsorganisation; Mitgliedschaft; Wirtschaftsreform; Privatisierung; Finanzföderalismus; China